Study on the interference of vaccine antibodies in the serological diagnosis of leptospirosis in cattle - Martinez, Mara Leila; Esteban, Micaela; Sanchez, Maria Cristina; Saraullo, Vanina Rosa; Hamer, Micaela; Samartino, Luis Ernesto; Brihuega, Bibiana Felicitas (International Leptospirosis Society, 2024)
Poster